2007
DOI: 10.1002/syn.20445
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and preliminary biological evaluation of 3‐[18F]fluoro‐5‐(2‐pyridinylethynyl)benzonitrile as a PET radiotracer for imaging metabotropic glutamate receptor subtype 5

Abstract: The metabotropic glutamate receptor subtype 5 (mGluR5) has been reported to be implicated in various neurological disorders in the central nervous system. To investigate physiological and pathological functions of mGluR5, noninvasive imaging in a living body with PET technology and an mGluR5-specific radiotracer is urgently needed. Here, we report the synthesis of 3-[(18)F]fluoro-5-(2-pyridinylethynyl)benzonitrile ([(18)F]FPEB) through a convenient thermal reaction as a highly specific PET radiotracer for mGlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
99
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 30 publications
2
99
0
Order By: Relevance
“…The synthesis and labeling of these tracers has been described by us (Brownell et al, 2003;Pellegrino et al, 2007;Wang et al, 2007). Regions of interest (ROIs) were delineated based on MRI high resolution anatomical images acquired on a Siemens 3T Trio system, as previously reported by our group (Jenkins et al, 2004;Sanchez-Pernaute et al, 2007) and anatomical atlas (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The synthesis and labeling of these tracers has been described by us (Brownell et al, 2003;Pellegrino et al, 2007;Wang et al, 2007). Regions of interest (ROIs) were delineated based on MRI high resolution anatomical images acquired on a Siemens 3T Trio system, as previously reported by our group (Jenkins et al, 2004;Sanchez-Pernaute et al, 2007) and anatomical atlas (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1e) as we have previously described in this model (Jenkins et al, 2004). To confirm that the change in [ 11 C]MPEPy binding reflected changes in mGluR5, we examined in 2 other primates, the distribution of the novel compound [ 18 F]FPEB (Hamill et al, 2005;Wang et al, 2007), which has exceptionally high affinity to mGluR5. The reported in vitro Bmax/Kd value based on the saturation binding studies in rhesus caudate-putamen tissue is 210 (Patel et al, 2007) and in vivo studies have shown that it is subgroup specific .…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…13 [ 18 F]FPEB was the most successful among the three mGluR5 tracers characterized in rhesus monkeys by Hamill et al 15 In preclinical studies, [ 18 F]FPEB displayed high specificity and affinity for mGluR5 as well as a regional uptake pattern consistent with the known distribution of mGluR5 in the brain. [16][17][18] Hence, [ 18 F]FPEB may have the potential to be used in humans to assess mGluR5 function in a variety of psychiatric and neurological disorders.…”
Section: Introductionmentioning
confidence: 99%